Maternal profiles and social determinants of malnutrition and the MDGs: What have we learnt?. (December 2016) - Tette, Edem; Sifah, Eric; Nartey, Edmund; Nuro-Ameyaw, Peter; Tete-Donkor, Pricilla; Biritwum, Richard
Abstract Background Maternal socio-demographic and health profiles are important determinants of malnutrition in children. In the 1990s, malnutrition was associated with low-birth-weight, young mothers and low maternal socio-economic status at Princess Marie Louise Children's Hospital (PML). It is not known how this has changed by efforts to achieve the Millennium Development Goals. We examined socio-demographic and health profiles of mothers of children with acute malnutrition and those without the condition to identify risk factors for malnutrition and focus on preventive efforts. Methods An unmatched case–control study was conducted in 2013 at PML, the largest facility for treating malnourished children in Ghana in 2013. Mothers of children with moderate and severe acute malnutrition were compared with mothers of well-nourished children. Weight-for-height was used to classify malnutrition. Record forms and a semi-structured questionnaire were used for data collection. An analysis was done with Stata 11.0 software. Results Altogether, 371 mothers were studied consisting of 182 mothers of malnourished children and 189 mothers of well-nourished children. Mothers of malnourished children were more likely to be unmarried or cohabiting, have lower family incomes, HIV infection and chronic disease. They were less likely to stay with or provide alternative care for their child. Awareness and use of social services, health insurance and a cash transfer programme were low. A remarkable reduction in the number of malnourished children occurred when families earned more than 250 USD a month. Over-nutrition was present in both groups of mothers. Conclusion Low family income, unmarried status and type of child care were the main social determinants of malnutrition. There appears to be a reduction in the number of other poor socio-demographic characteristics in both the study and control groups compared to results from a previous study at the same centre, probably because of efforts toward attaining the MDGs. These findings suggest that prevention and optimum management need to involve multidisciplinary teams consisting of health professionals, social workers and/or key workers to enable families at risk to access social care and social protection interventions (MDG 1). This will make the management of malnutrition more effective, prevent relapse, protect the next child and address maternal over-nutrition.